Screening for QTc prolongation during acute exercise in childhood acute lymphoblastic leukemia survivors. (11th May 2022) - Bertrand, E; Caru, M; Lemay, V; Andelfinger, G; Laverdiere, C; Krajinovic, M; Sinnett, D; Jacquemet, V; Curnier, D
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Institute of Cancer Research (ICR) of the Canadian Institutes ofHealth Research (CIHR), C17 Council Background: Anthracycline-related cardiotoxicity is a major cause of mortality and morbidity in childhood acute lymphoblastic leukaemia (ALL) survivors. Electrophysiologic complications and cardiac autonomic dysfunction are both known to be developed by childhood ALL survivors. Current methods for detection of cardiotoxicity have limitations, particularly due to their lack of sensitivity for early detection of subclinical cardiac dysfunction. Early detection of cardiac dysfunction remains a cardiologist's challenge and is essential to allow optimal therapeutic intervention. Purpose: This study aimed to observe ventricular repolarization during a maximal cardiopulmonary exercise test (CPET) in childhood ALL survivors. We hypothesized that cancer treatments lead to changes in ventricular repolarization that persist over time, and that the use of CPET allows the unmasking of electrophysiological abnormalities. Methods: A total of 250 childhood ALL survivors underwent a maximal CPET on an ergocycle, and their direct oxygen uptake was measured. All survivors were monitored continuously during the test using a 12-lead electrocardiogram. Measurements of the QT interval were completed at rest, at the end of each stage of the CPET, and during recovery. The QT interval was defined as the period from the onset of the Q-wave to the end of the T-wave, measured linearly. Values were corrected (QTc) using a specific group equation. To compare the effect of cardiorespiratory fitness on QTc during CPET, participants were divided in two groups according to the median of survivors' cardiorespiratory fitness (group A: <32.0 mL.kg-1.min-1; group B: ≥32.0 mL.kg-1.min-1). Results: All survivors (median age: 21 years, 51.5% male) included in the final analysis (n=200) performed a validated maximal CPET. At rest, the QTc interval was 379.1±32.2ms. None of the participants had a prolonged QTc during exercise (371.5±16.1ms, range 310.7-416.1ms). The mean QTc interval during CPET was not different between groups A and B (370.1±17.6ms and 373.0±14.4ms, p=0.218). Group A had a longer QT interval at low to moderate exercise intensities. During recovery, the QTc interval was 373.4.1±16.2ms. Conclusions: Cancer and anthracycline treatments have an impact on the cardiorespiratory system. Low cardiorespiratory fitness in childhood ALL survivors is associated with longer ventricular repolarization during exercise. These differences may be an indicator of altered cardiac function. This shows the importance of studying the response to exercise to improve early cardiac dysfunction detection, as well as documenting the autonomic nervous system response to exercise between survivors with lower and higher physical fitness.